2010
DOI: 10.1016/j.reprotox.2010.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Effects of prenatal exposure to a low dose atrazine metabolite mixture on pubertal timing and prostate development of male Long-Evans rats

Abstract: The present study examines the postnatal reproductive development of male rats following prenatal exposure to an atrazine metabolite mixture (AMM) consisting of the herbicide atrazine and its environmental metabolites diaminochlorotriazine, hydroxyatrazine, deethylatrazine, and deisopropylatrazine. Pregnant Long Evans rats were treated by gavage with 0.09, 0.87, or 8.73 mg AMM/kg body weight (BW), vehicle, or 100 mg ATR/kg BW positive control, on gestation days 15-19. Preputial separation was significantly del… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 35 publications
2
25
0
1
Order By: Relevance
“…For example, Rayner et al [14] reported that early life exposure of Wistar rats to atrazine increased the incidence of specific prostate inflammation in the adult. Similar results with adult male prostate inflammation in Long-Evans rats were obtained by Stanko et al [15] following late-gestational exposure to an atrazine metabolite mixture.…”
Section: Atrazinesupporting
confidence: 87%
“…For example, Rayner et al [14] reported that early life exposure of Wistar rats to atrazine increased the incidence of specific prostate inflammation in the adult. Similar results with adult male prostate inflammation in Long-Evans rats were obtained by Stanko et al [15] following late-gestational exposure to an atrazine metabolite mixture.…”
Section: Atrazinesupporting
confidence: 87%
“…Experimental evidence obtained from animal studies demonstrated that ATR could be an endocrine disrupter, which influences hormone production and, subsequently, reproduction [3,4,5,6,7]. As hormones play a major role in the development of the central nervous system (CNS), recent research has suggested that ATR is a dopaminergic system toxicant.…”
Section: Introductionmentioning
confidence: 99%
“…Shenoy (2012) showed that long-term exposure of adult male guppies to atrazine altered mating behaviors, which is possibly an activational effect. The effects of atrazine-exposure during early life stages have been studied on various end-points at later life stages, such as immunocompetence Rowe et al, 2006), development of reproductive tract (Stanko et al, 2010), survival, desiccation risk, and moisture-regulating behaviors Palmer, 2005, 2013); but the link between embryonic exposure to atrazine and the development (and later manifestation) of sexual behaviors is not clear.…”
Section: Introductionmentioning
confidence: 99%